A complementary approach of response surface methodology and an artificial neural network for the optimization and prediction of low salinity reverse osmosis performance. Issue 9 (September 2022) - Brooke, Ryan; Fan, Linhua; Khayet, Mohamed; Wang, Xu
Abstract: The treatment of saline water sources by reverse osmosis (RO) is being utilized increasingly to address water shortages around the world. The application of RO is energy-intensive; therefore, plant and process optimization are crucial. The desalination of low salinity water sources with total dissolved solids (TDS) of <5000 mg/L is less energy intensive than the desalination of highly saline seawater and brackish water. A gap exists in optimization studies on lower salinity water (TDS = 500–5000 mg/L). The novelty of the study is the development of a complementary approach using response surface methodology (RSM) and an artificial neural network (ANN) for performance modelling, optimization, and prediction of RO desalination of low salinity water. Feed water salinity, pressure, and temperature were controlled variables to model the performance of the RO system. A performance index incorporating salt rejection efficiency and permeate flux was used as the response target of the system. The optimal parameter combination within their modelled range for the best performance index occurred near the highest pressure input of 150.57 psi, at the temperature of 38.8 °C, and at the lowest feed salt concentration of 577 mg/L. Both the RSM and ANN models demonstrated high validity. The RSM and ANN showed R 2 values of 0.99 each and with a root mean square error of 2.41 and 5.85 respectively. The RSM showed a small benefit in model accuracy over the ANN, but the ANN has the benefit of not requiring the central composite design before experimentation and being a continuously improving prediction method as more data becomes available. Further applications of the optimization and modelling approach can be applied to RO system optimization considering membrane types and additional feedwater characteristics. Highlights: A complementary approach of response surface methodology (RSM) modelling and an artificial neural network (ANN) prediction model Modelling and optimizing the reverse osmosis (RO) desalination process of the low salinity water (TDS = 500–5000 mg/L) Sensitivity analysis of the RO desalination process parameters to the response target Discussion on the merits of each modelling methodology Abstract : Reverse osmosis; Response surface methodology; Artificial neural network; Low salinity.